Determinants of Poverty in Indonesia: An Empirical Evidence using Panel Data Regression - Firdaus, Adhityas; Dawood, Taufiq C.; Abrar, Muhammad (International Journal of Global Operations Research, 2021)
This study aims to analyze the effect of the rate of economic growth, average length of schooling, dependency ratio, and life expectancy on the percentage of poor people in Indonesia. This study uses panel data consisting of 34 provinces in Indonesia during the period 2016 to 2020. The analysis model used in this study is a panel data regression model. The results found in this study are variables that have a significant effect on the percentage of poor people in Indonesia are the average length of schooling, dependency ratio, and life expectancy. Meanwhile, the variable rate of economic growth has not had a statistically significant effect on the percentage of poor people in Indonesia. The variables of average length of school and life expectancy have a negative and significant effect on the percentage of poor people so that aspects of the quality of human resources represented by the level of education and health have an important role in poverty alleviation. Meanwhile, the dependency ratio has a positive and significant effect on the percentage of the poor, so various policies are needed to control population growth so that the productive population does not have too high a burden to bear the needs of the non-productive population.